1969
DOI: 10.1037/h0027971
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of decision-making skills learned in a counseling-like setting to similar and disimilar situations.

Abstract: Students were taught a specific decision-making strategy in a counselinglike setting. The degree to which the learned strategy transferred into similar and dissimilar situations was examined. Results: (a) directed practice was more effective than nondirected practice in facilitating the acquisition and transfer of the particular decision-making strategy employed; (b) sex of students did not appear to be significantly related to learning or transferring the required decision-making strategy; (c) differences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1971
1971
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Brief behavioral counseling methods have demonstrated an advantage over inactive control groups for increasing 11th graders' career exploratory behavior (e.g., Krumboltz & Thoresen, 1964;Meyer, Strowig, & Hosford, 1970) but have not proven effective on career decision making behavior (e.g., Bergland, Quartrano, & Lindquist, 1975). Conversely, decision making skills were taught successfully to 9th graders over 5 sessions (Evans & Cody, 1969). Directed instruction and counseling about career decision making had a greater impact on college students' decision making behavior than did individual counseling (Smith & Evans, 1973).…”
mentioning
confidence: 99%
“…Brief behavioral counseling methods have demonstrated an advantage over inactive control groups for increasing 11th graders' career exploratory behavior (e.g., Krumboltz & Thoresen, 1964;Meyer, Strowig, & Hosford, 1970) but have not proven effective on career decision making behavior (e.g., Bergland, Quartrano, & Lindquist, 1975). Conversely, decision making skills were taught successfully to 9th graders over 5 sessions (Evans & Cody, 1969). Directed instruction and counseling about career decision making had a greater impact on college students' decision making behavior than did individual counseling (Smith & Evans, 1973).…”
mentioning
confidence: 99%
“…This decision-making chart consisted of a number of different steps representing an integration of the decision-making steps described by Carkhuff (1973), Krumboltz (1966) and Evans and Cody (1969); 3. a career choice module in which the principles of decision-making are applied to career choice. The factors influencing career choice (values, abilities and interests) are explored.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…A final reason for using visuals is that research studies have demonstrated their effectiveness in test interpretation (Forster, 1969;Walker, 1965), stimulating vocational exploration (Hoyt, 1968;Krumboltz k Thoreson, 1964;Whitfield & Glaeser, 1969), decision-making (Boocock, 1967;Evans & Cody, 1969;Yabroff, 1964), personal growth (Kagan & Schauble, 1969), and interpersonal communication (Delaney & Heimann, 1966;Loeffler, 1970;Mehrabian, 1968).…”
Section: Adding a Visual Dimension To Counseling J O S I A H D I L L E Ymentioning
confidence: 99%